Perancangan Peta Risiko pada Perusahaan Perhiasan - Heryanto, Aldi; Arief, Khozin; Suwondo, Sulistia (Indonesian Accounting Literacy Journal, 2024)
Companies that are not able to manage their risks will have fatal consequences, plus at this time the pandemic has made the company increase the risks it has. This study aims to describe the design of a risk map in a jewelry company. This study uses a descriptive qualitative approach using data in the form of interviews, documentation, and observations. The data analysis technique used in this study is the analysis method of Miles and Hubberman (1984). The magnitude of the level of risk is reflected in the company's risk map, this amount is measured by the likelihood of a risk occurring and the impact of the risk if it occurs. There are 19 risks that may occur in the company, 9 risks at the low level, and 10 risks at the medium level.